Avaliação do efeito anti-tumoral de uma série de chalconas derivadas da quinoxalina sobre gliomas - estudo in vitro - Mielcke, Tânia Regina (2012)
Gliomas are the most common and devastating tumors of the central nervous system (CNS). Among the gliomas group, the GBM is the most prevalent, aggressive and deadly malignant. Many pieces of evidence point out the relevance of natural compounds for cancer therapy and prevention, including chalcones. Chalcones are group of natural precursors of flavonoid and display a wide variety of biological and pharmacological proprieties that include anti-proliferative and anti-cancer activities. This study aimed at evaluating the in vitro anti-proliferative activity and cell viability inhibition of nine quinoxaline derived chalcones, structurally based on the selective PI3Ky inhibitor AS605240. These synthetic compounds were tested at different time-periods of incubation (24, 48 e 72 h) and concentrations (0,1; 0,1; 1; 5 e 10 μg/mL) in glioma cell lines from human and rat origin (U-138 MG and C6, respectively). The results showed by MTT assay and cell couting revealed that four chalcones (compounds N2, N9, N10 and N12), displayed higher efficacies and potencies, being able to inhibit either cell proliferation or viability, in a time- and concentration dependent manner. These four compounds which present methoxy groups at A-ring and their efficacy was greater than that seen for the positive control compound AS605240. Flow cytometry analysis demonstrated that incubation of C6 cells with chalcone N9 led to G1 phase arrest, likely indicating an interference with apoptosis. Furthermore, chalcone N9 was able to visibly inhibit AKT activation, allied to the stimulation of ERK 1/2 MAP-kinase. The chalcones tested herein, especially those displaying a methoxy substituent at A-ring, might well represent promising molecules for the treatment of gliomas.